The Effect of Total Unemployment, Regional Minimum Wage, Population Density and Original Local Government Revenue to Human Development Index in Special Region of Yogyakarta 2014-2021 - Jesi Mlati Anggraini (Universitas Negeri Semarang, 2024)
The Province of the Special Region of Yogyakarta (DIY) is a province that ranks second on the Human Development Index (IPM) nationally and in all provinces on the island of Java. But there are still districts that have an average HDI below the provincial average HDI. The purpose of this research is to identify and analyze the factors that influence the Human Development Index (HDI) in the Province of DIY. The data used in this research is secondary data. This study used panel data regression analysis using the E-Views 9 application. This study used a combination of time series data and cross-sectional data from 5 districts/cities in the Province of DIY. The variables used in this study are HDI, the number of unemployed, UMR, PAD and population density. The estimation model used in this study uses the Fixed Effect Model (FEM). The results show that variables which have a significant effect on HDI are the number of unemployed, regional minimum wage (UMR), and population density. Meanwhile, Original Local Government Revenue (PAD) doesn't have a significant effect on HDI.